2015
DOI: 10.1016/j.seizure.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Extrafrontal structural changes in juvenile myoclonic epilepsy: A topographic analysis of combined structural and microstructural brain imaging

Abstract: In addition to structural changes in the thalamofrontal system, there was a conspicuous alteration of WM diffusivity in widespread extra-frontal areas and an associated decreased GM thickness in temporoparietal regions, including a significant reduction of hippocampal volume. These findings suggest that the pathophysiology of JME may be not confined to the thalamofrontal circuit but may also involve extensive areas of the extra-frontal network which encompasses temporo-parietal regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
(75 reference statements)
3
24
0
Order By: Relevance
“…The ventral posterolateral and ventromedial nuclei constitute the ventral posterior nucleus of the thalamus, which convey somatosensory information to somatosensory cortex of the parietal lobe . This is a consistent finding with a report that JME is associated with structural abnormalities in not only the thalamo‐frontal system but its adjacent regions, such as parietal cortex, based on gray matter thickness analysis . Another study with EEG functional connectivity also demonstrated that there was significant alteration among cortical areas related with sensory‐motor integration in the patients with JME .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The ventral posterolateral and ventromedial nuclei constitute the ventral posterior nucleus of the thalamus, which convey somatosensory information to somatosensory cortex of the parietal lobe . This is a consistent finding with a report that JME is associated with structural abnormalities in not only the thalamo‐frontal system but its adjacent regions, such as parietal cortex, based on gray matter thickness analysis . Another study with EEG functional connectivity also demonstrated that there was significant alteration among cortical areas related with sensory‐motor integration in the patients with JME .…”
Section: Discussionsupporting
confidence: 90%
“…22 This is a consistent finding with a report that JME is associated with structural abnormalities in not only the thalamo-frontal system but its adjacent regions, such as parietal cortex, based on gray matter thickness analysis. 23 Another study with EEG functional connectivity also demonstrated that there was significant alteration among cortical areas related with sensory-motor integration in the patients with JME. 24 The sensory-motor integration is a complex process that produces task-specific motor output based on selective and rapid integration of sensory information from multiple sources, during which the parietal cortex plays a pivotal role.…”
Section: Discussionmentioning
confidence: 96%
“…These findings could be related to the neuropsychological features of JME discussed below [6]. Whereas many studies indicate primary involvement of the frontal lobe, other findings showed participation of extensive extra-frontal networks encompassing conspicuous alteration of white matter diffusivity in temporo-parietal regions [46].…”
Section: Neuroimaging Findingsmentioning
confidence: 71%
“…Kim et al, [63] using the combined structural and diffusion tensor MRI analysis, found that 18 JME patients compared with 22 normal controls exhibited white matter alterations in the antero-superior corona radiata, both centroparietal regions, and the left temporal lobe. JME patients also had reduced gray matter thickness (right paracentral lobule, precuneus, dorsolateral parietal and inferior temporal cortex; left dorsolateral frontal and anterior temporal areas).…”
Section: Cerebrocortical Microdysgenesismentioning
confidence: 99%